ASPEK HUKUM WASIAT WAJIBAH UNTUK AHLI WARIS ANAK KANDUNG YANG BERBEDA AGAMA DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 51 K/AG/1999 - Darmawan, Wahyu (Universitas Wiralodra, 2021)
The barrier to inheritance or mawani 'al-irth is a barrier to the implementation of inheritance between the heir and his heirs. One of the barriers to the implementation of war is religious differences. Religious differences are one of the barriers that can cause a person to not be able to receive inheritance from someone who has died. The existence of these religious differences becomes a barrier to inheritance which has been explained based on a hadith of the Prophet Muhammad SAW: